COMPARATIVE STUDY OF PARACENTESIS, DIAGNOSTIC PERITONEAL LAVAGE, AND ULTRASONOGRAPHY IN THE MANAGEMENT OF PATIENTS OF BLUNT INJURY ABDOMEN – A STUDY FROM CENTRAL INDIA - CHANCHLANI, ROSHAN; CHANCHLANI, MADHU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Introduction: Blunt abdominal trauma comprises 1–1.5% of total admissions for trauma. In India every year more than a lakh persons die due to accidents. It is in fact the automobiles traveling at a greater speed than ever before that account for an amazing frequency of admissions in civilian hospitals. These injuries present a challenge to the most astute diagnostician, mainly because of the many organs involved, complexity of the hidden and vital structures involved and also because other frequently overshadow the early symptoms associated injuries to the head and chest. The figure is increasing every year, for example, from 1965 to 1966 and an increase by 8.4% was recorded. Methods: The present study consists of 70 cases of blunt abdominal trauma treated in surgical indoors of Hamidia Hospital and associated Gandhi Medical College, Bhopal within the period of 3 years. Abdominal paracentesis was done in all cases and diagnostic peritoneal lavage (DPL) done in those cases, where paracentesis was negative or doubtful. Ultrasonography was also done in almost all the cases admitted. Results: In our study, the accuracy and sensitivity of DPL marginally exceeds that of ultrasonography and accuracy and sensitivity of paracentesis is relatively less. Conclusion: Our study establishes that safety and accuracy of peritoneal tapping as a diagnostic aid in acute abdomen. It is particularly useful in several centers, where radiological facilities do not exist. Comparing all the above diagnostic tools, ultrasonography and DPL were considered are the most accurate, sensitive, and specific diagnostic modalities in cases of blunt injury abdomen.